Neuroendocrine tumors of the vagina - S. O. Nikogosyan; T. Sh. Tagibova; O. A. Anurova; A. A. Markovich; L. I. Korolenkova; V. V. Kuznetsov (ABV-press, 2015)
The paper covers the most important topographic-anatomic and histological characteristics of the vagina, gives general information on the epidemiology of primary vaginal cancer (VC), on the rules of its staging, describes the frequently encountered morphological types of this tumor, and indicates the properties and features of the course of neuroendocrine tumors (NETs), including the most common manifestations of carcinoid syndrome and the symptoms of tumor hypersecretion of a number of biologically active substances. It also indicates the most common sites of NETs, the rules of their classification according to the grade and mitotic activity of tumor cells, as well as major methods for biochemical and radiological diagnosis. The immunohistochemical NET markers that can diagnose VC, their physiological role, sensitivity, and specificity, as well as the possibility of determining them in the body's biological environments in order to increase physicians' awareness are described in detail and the main aspects of tumor immunohistochemical staining are denoted. The role of circulating tumor cells as a promising method to specify the extent of NETs is defined. The paper gives epidemiological information on the development of vaginal NET and summarizes the available data by their clinical course and treatment results. It provides current guidelines on the required treatment volume and specifies the role of surgical intervention and the necessary volume if the intervention is expedient. It sets forth the up-to-date guidelines for chemotherapy for small cell tumors, as well as VC, which includes the specific features of managing patients with tumor recurrences depending on the time of their development.